Development of Phyllanthus emblica (L) fruit as a carrier for EGCG: Interaction and in vitro digestion study. Issue 7 (8th April 2019) - Du, Zhizheng; Liu, Jianghong; Li, Yongyu; Lin, Jinke; Sun, Yun; Guo, Yaling; Wu, Liangyu
Abstract: Emblica fruit is an undervalued and underutilized nature product. The emblica fruit materials with different processing pretreatments were prepared and used for incorporation of Epigallocatechin gallate (EGCG). The adsorption behaviors of EGCG onto emblica fruit were studied over the EGCG concentration range from 50 to 800 mg/L and different temperatures (25, 40, and 55°C). The results showed that both of Langmuir and Freundlich models were suitable for describing the isothermal adsorption of EGCG onto emblica fruit materials, and an excellent fitness to the pseudo‐second order model was observed. Thermodynamics study suggested that the adsorption process was endothermic and spontaneous. All the processed emblica fruit materials greatly retarded the degradation of EGCG during the in vitro gastrointestinal digestion, with the recovery rate up to 52% compared with 38% of unprotected EGCG. This result indicates that emblica fruit is a promising food matrix for delivering EGCG with the enhancement of EGCG stability against digestion degradation. Practical applications: The physicochemical properties and adsorption capacities of pretreated emblica fruit materials are measured. The emblica fruit elevated the stability of EGCG against in vitro digestion degradation. This provides a promising approach for commercial and industrial utilization of emblica fruit, also an optional way for the improving EGCG bioavailability.